Apresentação do Dossiê (segunda parte). O Fédon de Platão. Conferência da Sociedade Brasileira de Platonistas (SBP) - Xavier, Dennys Garcia (Revista Archai, 2016)
Dossier’s Presentation (second part): Plato’s Phaedo. Platonists Brazilian Society Conference